The effect of using an educational program for the speed of motor response according to audiovisual responses on the accuracy of receiving the ball for some types of passing in basketball: تأثير استخدام برنامج تعلیمی لسرعة الاستجابة الحركية وفقاً للإستجابات السمعية والبصرية في دقة استلام الكرة لبعض انواع المناولات في كرة السلة - Karim, Omar A. (Humanities Journal of University of Zakho, 2024)
The developments in the game of basketball resulted from studies and research in this area. Receiving the ball is the only skill researchers have not addressed as far as the researcher knows. It is one of the basic offensive skills important, whether alone when the player receives the ball or maintains it or in the next step when the player uses the ball for dialogue, handling, or scoring. The idea of using kinetic response speed exercises came to develop the accuracy of receiving the ball for some handlings in basketball, as the research aims to detect the effect of the motor response speed educational program according to audiovisual responses on the accuracy of receiving the ball for some types of handlings in basketball. An experimental approach was used on a sample of the Soran University basketball team players, consisting of (16) players. (4) Players were excluded for the purpose of an exploratory experiment. As for the remaining number of the sample, it was (12) players who were divided into two groups, each group of (6) players. An educational program was used for the speed of the motor response with two experimental groups, the first according to audio responses and the second according to visual responses. The evaluation of the skillful performance art was used as a research tool to measure receiving the ball for some basketball tackles., and the researcher used the program (SPSS) to process statistical data. Several conclusions were reached, including: The results showed that using the educational program for motor speed according to auditory responses positively and effectively affected the accuracy of receiving the ball for some passes (chest pass - bounce pass, and overhead pass) in basketball. The results showed that using the educational program for motor response speed according to the visual responses positively and effectively affected the accuracy of receiving the ball for some passes (chest pass - bounce pass, and overhead pass) in basketball The results showed that there are no differences in the post-test between the two experimental groups in the accuracy of receiving the ball for passing (chest-bounce-over the head) in basketball.